2019
DOI: 10.1038/s41598-019-45262-4
|View full text |Cite
|
Sign up to set email alerts
|

Sniffer cells for the detection of neural Angiotensin II in vitro

Abstract: Neuropeptide release in the brain has traditionally been difficult to observe. Existing methods lack temporal and spatial resolution that is consistent with the function and size of neurons. We use cultured “sniffer cells” to improve the temporal and spatial resolution of observing neuropeptide release. Sniffer cells were created by stably transfecting Chinese Hamster Ovary (CHO) cells with plasmids encoding the rat angiotensin type 1a receptor and a genetically encoded Ca2+ sensor. Isolated, cultured sniffer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…It was recently demonstrated that SFO neuronal activation is able to elicit release of ANG II into other brain areas 42 . Both PVN and ARC, the key brain regions for metabolic control and food regulation, receive direct projections from the SFO and are highly responsive to ANG II via AT 1 Rs 6–8 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was recently demonstrated that SFO neuronal activation is able to elicit release of ANG II into other brain areas 42 . Both PVN and ARC, the key brain regions for metabolic control and food regulation, receive direct projections from the SFO and are highly responsive to ANG II via AT 1 Rs 6–8 .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that SFO neuronal activation is able to elicit release of ANG II into other brain areas. 42 Both PVN and ARC, the key brain regions for metabolic control and food regulation, receive direct projections from the SFO and are highly responsive to ANG II via AT 1 Rs. [6][7][8] We also found a significant increase in the Agtr1a mRNA expression in the PVN after 48 h of fasting in rats, confirming previous findings that indicated increased AT 1 R binding after 2 weeks of severe food restriction.…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available techniques used to detect and measure the release of peptides or neurotransmitters from biological preparations, such as microdialysis, high-pressure liquid chromatography, or electrochemical techniques, offer great levels of sensitivity but lack the temporal and spatial resolution required to study quantal release from single cells [69, 70]. Sniffer cells can be used as biosensors to detect the release of peptides or neurotransmitters with optimal sensitivity and spatiotemporal resolution.…”
Section: Genetic Labelling Methodsmentioning
confidence: 99%
“…This supports the idea that the SFO senses changes in [Na + ] to regulate sodium appetite. In addition to hormonal actions, there is some evidence that ANGII acts as a neurotransmitter [ 116 , 117 , 118 , 119 , 120 ] and is therefore capable of stimulating AT1R in areas within the blood–brain barrier. The SFO has dense angiotensin-sensitive projections to the BNST [ 52 , 121 ] and PVN [ 117 , 118 ].…”
Section: Neural and Hormonal Control Of Sodium Intakementioning
confidence: 99%